Application of PRECEDE-PROCEED Planning Model in Transforming the Clinical Decision Making Behavior of Physical Therapists in Myanmar - Hlaing, Phyu Hnin; Sullivan, Patricia E.; Chaiyawat, Pakaratee (Frontiers in Public Health, 2019)
Introduction Physical therapists in Myanmar use a prescriptive model of Clinical Decision Making (CDM). Improving CDM effectiveness is one essential factor in professionalizing practice and enhancing patient outcomes. This study assesses the changes in CDM skills and behaviors using the PRECEDE-PROCEED planning Model (PPM). Methods In the PRECEDE planning phases, we investigated the current clinical decision making knowledge and process, clinical practice culture and contributing factors of CDM among Myanmar physical therapists. A qualitative approach consisted of 18 in-depth interviews and one focus group discussion was used. In the PROCEED evaluation and implementation phases, we developed and presented the CDM educational book at CDM workshop, which was a 4-day intensive program in Yangon, Myanmar with 34 participants. The participant’s CDM knowledge and processes were assessed before and after the educational program to explore the potential impact on implementing CDM which can ultimately improve patient care in the health settings of Myanmar. Results In the PRECEDE phases, we explored the predisposing and reinforcing factors of Myanmar physical therapists’ CDM. We found that deliberative decision making process that is used internationally were not followed by Myanmar physical therapists who followed the physician’s prescriptions. Teaching and learning emphasize a stimulus-response-repeat-outcome cycle without internal processing or application to clinical situations. Using the PROCEED model, we developed a 14 chapters CDM workbook and a four-day workshop as a behavioral change intervention. Participants’ prior technical CDM behavior was transformed into professional CDM behavior that included an understanding of clinical practice models and improvement in the cognitive process of CDM processes. The workbook coupled with the intensive active-learning, hands-on workshop of examination and intervention procedures were effective in improving CDM. Discussion The application of PPM provided a thorough understanding of current CDM process of Myanmar therapists and aided in the development of the tailored CDM educational program to improve participants’ CDM. Using the PPM model for developing a set of Physical Therapy educational content and curriculum was new. The application of PPM was beneficial to use accepted clinical practice models, standardized tests and measures, set goals and clinical outcomes, reassessed to determine change and implement evidence-based practice.